ІНТЕЛЕКТОКОРИСТУВАННЯ ЯК ФУНКЦІЯ ЖИТТЄВОЇ АКТИВНОСТІ СОЦІУМУ (International Journal of Innovative Technologies in Economy, 2018)
The article proposes an original definition of the processes of proper use of the intelligence of the individual, as well as of human communities, as the main task of their survival in modern conditions. For this, the model of the human person is presented as a bio-socio-economical element of living nature, on the basis and with the participation of which the primary element (person) and secondary element (a couple of persons) are formed elements of society, which forms the social environment. Four possible variants of functional-intellectual interaction of the primary elements in the modes "subject-object", "subject-subject", "object-subject" and "object-object" are analyzed. Demonstrated that due to the proper organization of this process there is a gradual and steady improvement and development of society, and improper condition inhibits development processes, leads to stagnation, to degradation, decline and disappearance of society. In this regard, the problem of improving the management of the use of intellectual resources of socio- economic systems through the improvement of the processes and procedures of intellectual use, deserves a problematic issue of further sustainable development of society.